THE EFFECT OF E-FILLING IMPLEMENTATION, TAX KNOWLEDGE AND THE ROLE OF ACCOUNT REPRESENTATIVES ON INDIVIDUAL TAXPAYER COMPLIANCE AT THE CILEGON PRATAMA TAX OFFICE SERVICE (KPP PRATAMA CILEGON) - Dharma Putri, Asti Lintang; Ginanjar, Seandy; Andi (PT Larva Wijaya Penerbit, 2023)
This study aims to examine the effect of the application of e-filling, tax knowledge, and the role of account representative on tax compliance in the Pratama Tax Office (KPP) Cilegon. This research uses quantitative methods with survey research forms. This study uses data in the form of primary data obtained from the distribution of questionnaires. The sample used is an individual taxpayer who uses e-filling registered at the Pratama Tax Office (KPP) Cilegon. The sampling technique used was purposive sampling. Of the 120 questionnaires distributed, the number of questionnaires that can be processed are 100 questionnaires. The analytical method used is multiple linear regression analysis. The data in this study were processed using Statistical Package For Social Science (SPSS.20). The results of this study reveal that all independent variables in this study are the application of e-filling, knowledge of taxation, and the role of account representatives influencing taxpayer compliance.